2015
DOI: 10.15252/embr.201540750
|View full text |Cite
|
Sign up to set email alerts
|

miR‐9‐5p suppresses pro‐fibrogenic transformation of fibroblasts and prevents organ fibrosis by targeting NOX 4 and TGFBR 2

Abstract: Uncontrolled extracellular matrix (ECM) production by fibroblasts in response to injury contributes to fibrotic diseases, including idiopathic pulmonary fibrosis (IPF). Reactive oxygen species (ROS) generation is involved in the pathogenesis of IPF. Transforming growth factor-b1 (TGF-b1) stimulates the production of NADPH oxidase 4 (NOX4)-dependent ROS, promoting lung fibrosis (LF). Dysregulation of microRNAs (miRNAs) has been shown to contribute to LF. To identify miRNAs involved in redox regulation relevant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 84 publications
6
87
0
Order By: Relevance
“…Likewise, levels of the miR-17 ~ 92 cluster were also decreased in IPF patients, probably caused by a feedback loop involving reduced targeting of DNA methyltransferase (DNMT1) leading to altered DNA methylation patterns at the miR-17~92 promoter (Dakhlallah et al, 2013). Moreover, both miR-9-5p and miR-153 repressed experimental fibrosis in cells and mice by targeting the 3′ UTR of TGF-β receptor 2 (TGFBR2), a mechanism similar to that of miR-1343 discussed previously (Fierro-Fernández et al, 2015;Liang et al, 2015;Stolzenburg et al, 2016). Though miR-153 levels were decreased in the cell-based model of IPF, consistent with the anti-fibrotic role of this miRNA hypothesized by Liang and colleagues, miR-9-5p levels were increased in human pulmonary fibrosis samples (Fierro-Fernández et al, 2015;Liang et al, 2015).…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 52%
See 1 more Smart Citation
“…Likewise, levels of the miR-17 ~ 92 cluster were also decreased in IPF patients, probably caused by a feedback loop involving reduced targeting of DNA methyltransferase (DNMT1) leading to altered DNA methylation patterns at the miR-17~92 promoter (Dakhlallah et al, 2013). Moreover, both miR-9-5p and miR-153 repressed experimental fibrosis in cells and mice by targeting the 3′ UTR of TGF-β receptor 2 (TGFBR2), a mechanism similar to that of miR-1343 discussed previously (Fierro-Fernández et al, 2015;Liang et al, 2015;Stolzenburg et al, 2016). Though miR-153 levels were decreased in the cell-based model of IPF, consistent with the anti-fibrotic role of this miRNA hypothesized by Liang and colleagues, miR-9-5p levels were increased in human pulmonary fibrosis samples (Fierro-Fernández et al, 2015;Liang et al, 2015).…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 52%
“…Moreover, both miR-9-5p and miR-153 repressed experimental fibrosis in cells and mice by targeting the 3′ UTR of TGF-β receptor 2 (TGFBR2), a mechanism similar to that of miR-1343 discussed previously (Fierro-Fernández et al, 2015;Liang et al, 2015;Stolzenburg et al, 2016). Though miR-153 levels were decreased in the cell-based model of IPF, consistent with the anti-fibrotic role of this miRNA hypothesized by Liang and colleagues, miR-9-5p levels were increased in human pulmonary fibrosis samples (Fierro-Fernández et al, 2015;Liang et al, 2015). These findings underscore the complex mechanisms driving miRNA regulation and indicate that miRNA mis-expression may either be a driver or a consequence of disease.…”
Section: Idiopathic Pulmonary Fibrosismentioning
confidence: 67%
“…29 It has been shown that activation of TGF-b-Smad signaling induces the expression of specific miRNAs that, in turn, may modulate TGF-b-Smad signaling in a feedback manor. [30][31][32] For example, TGF-b1 induces miR-9-5p expression, while overexpression of miR-9-5p in lung fibroblasts inhibits TGFbRII expression and prevents myofibroblast differentiation, ECM deposition, and organ fibrogenesis. 31 Here, we found that TGF-b1 induces a decrease in miR-18a-5p.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] For example, TGF-b1 induces miR-9-5p expression, while overexpression of miR-9-5p in lung fibroblasts inhibits TGFbRII expression and prevents myofibroblast differentiation, ECM deposition, and organ fibrogenesis. 31 Here, we found that TGF-b1 induces a decrease in miR-18a-5p. In order to clarify how miR-18a-5p regulates TGF-b-Smad signaling, we first measured TGF-b1.…”
Section: Discussionmentioning
confidence: 99%
“…Given the important role of TGF-β on EMT process, therapeutic interventions that utilize small chemicals or genetic technology to interfere with TGF-β signaling at various transduction steps have been developed to reverse the established fibrosis (Chakraborty et al 2014;Fukunaga et al 2015). For instance, miRNA or chemokine was reported to reverse fibrosis in the rodent animals or cell lines in vitro (Fierro-Fernandez et al 2015;O'Beirne et al 2015). Apart from the genetic approaches, small chemicals targeting TGF-β signaling cascade have strong therapeutic potential in preclinical settings (Nanthakumar et al 2015).…”
Section: Discussionmentioning
confidence: 99%